The effects of MDMA on brain: An in vivo study in rats - Zakaria, Fatin Haniza; Abu Bakar, Nor Hidayah; Mohamad, Nasir; Abdul Latif, Ahmad Zubaidi; Mor Japar Khan, Ed Simor Khan; Wan Ahmad, Wan Amir Nizam (International Journal of Pharmaceutical Research and Allied Sciences (IJPRAS), 2018)
Background and objective : 3, 4-Methylenedioxymethamphetamine (MDMA) is a powerful central nervous system stimulant that acts by increasing the activity of several neurotransmitter systems. This study aimed to investigate the effect of different doses of MDMA on the level of serotonin in the brain measured from the cerebrospinal fluid (CSF) and their effects on the neurons. Materials and methods : Twenty-six adult male rats were divided into 4 groups. The control group (n=7) received intraperitoneal (IP) injections of 1 mL/gm normal saline twice daily for one week. The MDMA treated groups (n= 6/7) were further subdivided into 3 groups, each receiving 5, 10 or 15mg/kg MDMA intraperitoneal (IP) injections twice daily for one week ; respectively. 24 hours after the last injection of the rats, the CSF was collected. The brains were dissected and processed for paraffin sections and stained by cresyl etch violet stain. Histology, morphometry and statistical analysis were done. Results : The administration of different doses of MDMA significantly increased the level of serotonin in comparison with the control group. The morphometry study indicated that the number of intact neurons in the hippocampus significantly decreased following the administration of different doses of MDMA comparing to the control group. The results also indicated that there was a strong negative correlation between the serotonin levels and the number of intact neurons. Conclusion : MDMA administration even at a low dose had degenerative effects on the neurons in the hippocampus as evidenced by morphometric study, and the intake should be avoided.